# Write x^{2 }- 6x + 7 = 0 in the form (x - a)^{2} = b, where a and b are integers.

**Solution:**

Given that: x^{2 }- 6x + 7 = 0

To convert the above equation into a perfect square we add 9 on the left hand side and hence we have to subtract too on the same side.

We have

x^{2} - 6x + 9 - 9 + 7 = 0

(x^{2} - 6x + 9) - 9 + 7

By Splitting the middle term, we get

x^{2} - 3x - 3x + 9 - 2 = 0

x(x - 3) - 3(x - 3) = 2

(x - 3)(x - 3) = 2

(x - 3)^{2} = 2

## Write x^{2} - 6x + 7 = 0 in the form (x - a)^{2} = b, where a and b are integers.

**Summary:**

The given equation x^{2} - 6x + 7 = 0 is written as (x - 3)^{2} = 2.

Math worksheets and

visual curriculum

visual curriculum